Bifunctional CO2 Plasma Treatment at the i/p Interface Enhancing the Performance of Planar Silicon Heterojunction Solar Cells. Issue 12 (10th February 2021) - Yan, Lingling; Huang, Shenglei; Ren, Huizhi; Zhang, Dekun; Liu, Wenzhu; Zhao, Ying; Zhang, Xiaodan
Abstract : Hydrogenated nanocrystalline silicon (nc‐Si:H) or hydrogenated nanocrystalline silicon oxide (nc‐SiO x :H) as window layers have ample potential to improve the short‐circuit current density ( J SC ) of silicon heterojunction (SHJ) solar cells due to their wide optical bandgap. However, the growth of their nanocrystals within a 20 nm‐thickness on intrinsic hydrogenated amorphous silicon ( i ‐a‐Si:H) poses a challenge. Plasma treatment (PT) after i ‐a‐Si:H deposition is usually used to improve passivation performance. Herein, the i / p interface is subjected to CO2 PT: a 20 s post CO2 PT is proven to be beneficial in obtaining improved passivation performance. This can be achieved by activated hydrogen which can be diffused to the wafer surface and can saturate the dangling bonds on it. Extending the CO2 PT time from 20 to 40 s, the oxygen (O) insertion into i ‐a‐Si:H starts to increase slowly, which leads to marginal change of microstructure in the p layer. Strained SiSi bonds by oxygen incorporation into the a‐Si:H network generate nucleation sites and consequently accelerate the nucleation of p ‐nc‐Si:H on i ‐a‐Si:H. Finally, it is demonstrated that the power conversion efficiency (PCE) of planar SHJ solar cells is enhanced from 12.65% to 19.06% by a 20 s CO2 PT at the i / p interface. Abstract : A 20 s CO2 plasma treatment (PT) at the i/p interface is useful for improving passivation performance, and oxygen (O) insertion into intrinsic hydrogenated amorphous silicon ( i ‐a‐Si:H) promotes rapid nucleation of p ‐type hydrogenated nanocrystalline silicon ( p ‐nc‐Si:H) on i ‐a‐Si:H. Finally, the corresponding power conversion efficiency (PCE) of planar silicon heterojunction (SHJ) solar cells is enhanced from 12.65% to 19.06%.